Kesetaraan Gender dalam Budaya Sibaliparri Masyarakat Mandar - Abdul Latief; Siti Maryam; Muh. Yusuf (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
Gender is a sex differences based on culture, where men and women are distinguished according to their respective roles that are constructed by local culture related to the role of nature, position and status in society.In the gender concept, the difference between men and women based on social and cultural construction of the mandar community has work behavior or culture that they are familiar with sibaliparri. Theresearch problemof this study is whether the culture of sibaliparri in which there is a gender equality.The motive of this research is to reveal how gender equality between a couple husband and wife in mandar community household based on sibaliparri cultural values. To find the answer of the research problem, a qualitative descriptive study is needed. Data collection methods used was field observations, interviews and literature study. The results showed that gender equality in mandar society was manifested in sibaliparri culture, namely the existence of mutual assistance between husband and wife and involving all family members.